Proof-of-concept study of the TriBot: a robot-based test setup for biotribological analyses of curved articular surfaces - de Roy, Luisa; Roderigo, Moritz; Schwer, Jonas; Schlickenrieder, Klaus; Ignatius, Anita; Seitz, Andreas Martin (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionInvestigations on the articular cartilage (AC) frictional properties contribute to a better understanding of knee joint functionality. We identified the need for a tribological setup that allows for friction measurements on curved AC surfaces, without disrupting its structural integrity, under orthogonal contact conditions and controlled normal force application. Therefore, a robotic-based tribometer–the TriBot–was developed and validated in a two-part proof-of-concept study.MethodsFirst, the friction coefficients of polyoxymethylene pins on three different polyamide (PA) shapes were determined for validation purposes. Second, the frictional properties on porcine tibial plateaus were investigated. Trajectories on the medial and the lateral tibial surface were tested in the intact cartilage state and after inducing an anteromedial local defect.ResultsNo significant differences in the friction coefficients of the PA samples were found. Inducing an anteromedial cartilage defect significantly increased friction on the affected trajectories (+30%, p < 0.05).DiscussionOur findings showed that the robotic tribometer is suitable for friction measurements on complexly shaped samples and that the system can detect differences in cartilage friction due to structural tissue damage. Overall, the robotic tribometer has the potential to advance our understanding of the knee joint’s friction-related functionality.